Etanercept Inhibits B Cell Differentiation by Regulating TNFRII/TRAF2/NF-κB Signaling Pathway in Rheumatoid Arthritis - Cai, Xiao-Yu; Zhu, Yue; Wang, Chen; Tang, Xiao-Yu; Han, Le; Shu, Jin-Ling; Zhang, Xian-Zheng; Liang, Fa-Qin; Ge, Jing-Ru; Xu, Li; Mei, Dan; Zhang, Ling-Ling; et al. (Frontiers in Pharmacology, 2020)
Objective: To explore the role of B cells in rheumatoid arthritis (RA) and the potential effects and mechanisms of etanercept on B cells. Methods: In RA patients, the levels of TNF-α and BAFF were detected by ELISA. The percentage of B cell subsets was measured by flow cytometry. Laboratory indicators (rheumatoid factor, C-reactive protein, erythrocyte sedimentation rate) and clinical indicators (disease activity score in 28 joints, health assessment questionnaire score, swollen joint counts, tender joint counts) were measured. The correlation between B cell subsets and laboratory indicators or clinical indicators was analyzed. In mice, B cells proliferation was detected by CCK-8 kit. The expression of TNFRII and the percentage of B cell subsets in spleen were detected by flow cytometry. The expressions of TRAF2, p38, P-p38, p65, P-p65 in B cells were detected by WB. Results: The percentage of CD19-CD27+CD138+ plasma B cells was positively correlated with ESR or RF. Etanercept could decrease the percentage of CD19+ total B cells, CD19+CD27+ memory B cells and CD19-CD27+CD138+ plasma B cells, reduce the levels of TNF-α, BAFF, relieve clinical and laboratory indicators in RA patients. In addition, etanercept could inhibit the proliferation of B cells, bate the differentiation of transitional B cells to mature B cells, down-regulate the expression of TNFRII, TRAF2, P-p38, P-p65 in B cells. Conclusion: B cells act a key role in the pathogenesis of RA. Etanercept inhibits B cells differentiation by down-regulating TNFRII/TRAF2/NF-κB signaling pathway.